Herbicide alternatives for desiccation of fallow areas - Ribeiro, Daniele Ferreira; Côrrea, Fernando Rezende; Silva, Nelmício Furtado da; Cavalcante, Wendson Soares da Silva; Rodrigues, Estevão (Brazilian Journal of Science, 2023)
Weeds directly interfere in agricultural production, in addition to serving as hosts for pests and diseases. The period prior to sowing and crop emergence is one of the most important, so pre-sowing desiccation is essential. Thus, establishing alternatives for a broader spectrum of weed control is essential for the sustainability of the management system. Thus, it aimed to evaluate herbicide molecules for weed control in desiccation management in fallow areas. The experiment was carried out in the experimental area of the Teaching and Research Farm at UniBRÁS College, in the rural area of the municipality of Rio Verde, Goiás State, Brasil. The experimental design used was in randomized blocks with 9 treatments and 4 replications. The experimental unit consisted of a rectangle of 2 x 12.5 m respectively per treatment, making up an area of 25 m² per experimental unit and a total area of 800 m² for the test. The treatments were: (T1) Control, (T2) Diquat, (T3) Diquat + Glyphosate, (T4) Saflufenacil, (T5) Saflufenacil + Glyphosate, (T6) Glufosinate, (T7) Glufosinate + Glyphosate, (T8) Carfentrazone and (T9) Carfentrazone + Glyphosate. Weed control evaluations were carried out at 2, 5, 7, 10, 14 and 21 days after application, carried out by visual scale with the attribution of grades from 0 to 100%. Data were subjected to analysis of variance by the F test and means compared by Tukey’s test at 5% probability. The T7 treatment promoted 94.5% weed control, the T6 and T10 treatments also showed high efficiency in the management of desiccation although inferior.